2018
DOI: 10.1371/journal.pone.0204653
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale mitochondrial DNA analysis reveals new light on the phylogeography of Central and Eastern-European Brown hare (Lepus europaeus Pallas, 1778)

Abstract: European brown hare, Lepus europaeus, from Central and Eastern European countries (Hungary, Poland, Serbia, Lithuania, Romania, Georgia and Italy) were sampled, and phylogenetic analyses were carried out on two datasets: 1.) 137 sequences (358 bp) of control region mtDNA; and 2.) 105 sequences of a concatenated fragment (916 bp), including the cytochrome b, tRNA-Thr, tRNA-Pro and control region mitochondrial DNA. Our sequences were aligned with additional brown hare sequences from GenBank. A total of 52 and 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Particularly the study of Djan et al [21] also suggested a long lasting ancestral population history in the Anatolian Peninsula [29], a subsequent population expansions in the southeastern and southern Balkans, and a relative young population expansion into central and northern/northwestern continental Europe. Additional population expansion in eastern Europe, probably from southwestern Eurasian regions with lineages phylogenetically closely related to those found on the Anatolian Peninsula and other regions in the Near East were particularly suggested by Ashrafzadeh et al [20]. Those latter mentioned lineages have, however, so far not managed to expand much towards central Europe; rather their western front does not seem to extend much further west than eastern Poland and the Ukraine.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Particularly the study of Djan et al [21] also suggested a long lasting ancestral population history in the Anatolian Peninsula [29], a subsequent population expansions in the southeastern and southern Balkans, and a relative young population expansion into central and northern/northwestern continental Europe. Additional population expansion in eastern Europe, probably from southwestern Eurasian regions with lineages phylogenetically closely related to those found on the Anatolian Peninsula and other regions in the Near East were particularly suggested by Ashrafzadeh et al [20]. Those latter mentioned lineages have, however, so far not managed to expand much towards central Europe; rather their western front does not seem to extend much further west than eastern Poland and the Ukraine.…”
Section: Discussionmentioning
confidence: 89%
“…The latter has acted as a source region for further colonization of the Balkan Peninsula and later on–after the last glacial maximum (ca. 18.000 ybp)–to central Europe [2022, 24]. Particularly the study of Djan et al [21] also suggested a long lasting ancestral population history in the Anatolian Peninsula [29], a subsequent population expansions in the southeastern and southern Balkans, and a relative young population expansion into central and northern/northwestern continental Europe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clade B likely colonized Europe along a southern route. This route was probably via the Bosphorus junction while sea levels had receded during glacial maxima, as has been inferred for other species [14,30,64,65]. This could explain why the diversification in clade B preceded the one in clade C by ~5 ky (Fig.…”
Section: Implications For European Populations Of Lynx Lynxmentioning
confidence: 59%